On the novel wave behaviors to the coupled nonlinear Maccari's system with complex structure - Baskonus, Haci Mehmet; Sulaiman, Tukur Abdulkadir; Bulut, Hasan (Elsevier Gmbh, 2017)
In this paper, we seek for the new soliton solutions to the coupled nonlinear Maccari's system by using sine-Gordon expansion method. Sine-Gordon expansion method is based on sine-Gordon Eq. (2.1) and a travelling wave transformation. We obtain new complex hyperbolic functions solutions to this system with help of Wolfram Mathematica 9, we also plot 3-dimensional and 2-dimensional graphics to some obtained solution using the same program in Wolfram Mathematica 9. Finally, we submit a comprehensive conclusions. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Sine-Gordon expansion method; Coupled nonlinear Maccari's system; Complex hyperbolic function structures